Answer:(9,-5)
Step-by-step explanation: trust me
The lines that intersect is B
Answer:
4
Step-by-step explanation:
If Judge is x years old and Eden is 6 years older, then Eden is x + 6 years old.
The second part tells us that Eden will be twice as old as Judge in two years.
This means that in two years: (Eden's age) = 2 * (Judge's age).
Since we know that Eden's age can be represented as x + 6 and Judge's age can be represented as x, we can write this: x + 6 = 2 * x
Simplify the equation:
x + 6 = 2x
6 = x = Judge's age (in two years)
If Judge is 6 two years later, then he must be 4 now.
To check our work, we can just look at the problem. Judge is 4 years old and Eden is 6 years older than Judge (that means Eden is 10 right now). Two years later, Eden is 12 and Judge is 6, so Eden is twice as old as Judge. The answer is correct.
y = 3(x + 4)^2 + 31
Step-by-step explanation:
We can convert the given quadratic equation into its vertex form by completing the square:
y = 3x^2 + 24x + 43
= 3(x^2 + 8x) + 43
= 3(x^2 + 8x + 4) + 31
= 3(x + 4)^2 + 31
This is the vertex form of the given quadratic equation with (-4, 31) as its vertex
Answer:
37/40
Step-by-step explanation: